2018
DOI: 10.1097/ico.0000000000001668
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness Increase Due to Stromal Thickening With Diabetic Peripheral Neuropathy Severity

Abstract: This study demonstrates that CCT increases with DPN severity because of an increase in stromal thickness. CCT increase associated with DPN has important clinical implications including glaucoma progression, keratoconus susceptibility, and intraocular pressure assessment and should be accounted for when evaluating patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…Santiagu et al [86] found that diabetes during pregnancy also does not seem to influence CCT. In a recent article, Kumar et al [87] showed that CCT increases in relation to the severity of peripheral diabetic neuropathy due to an increase in stromal thickness. Other studies, however, have not found an increase in CCT in cases of T1D [88] or T2D patients [8991].…”
Section: Diabetes and Corneal Stromamentioning
confidence: 99%
“…Santiagu et al [86] found that diabetes during pregnancy also does not seem to influence CCT. In a recent article, Kumar et al [87] showed that CCT increases in relation to the severity of peripheral diabetic neuropathy due to an increase in stromal thickness. Other studies, however, have not found an increase in CCT in cases of T1D [88] or T2D patients [8991].…”
Section: Diabetes and Corneal Stromamentioning
confidence: 99%
“…A relationship between the cornea thickening and the increase in distal latency or a conduction velocity decrease both in motor and sensory fibers of the selected nerves was observed. So far, an association between CCT increase and diabetic peripheral neuropathy severity only in the adults with type 1 and type 2 diabetes has been described [21]. The authors demonstrated the increase in CCT values and referred it to the results of stromal thickening obtained by using the corneal confocal microscopy [21].…”
Section: Discussionmentioning
confidence: 97%
“…So far, an association between CCT increase and diabetic peripheral neuropathy severity only in the adults with type 1 and type 2 diabetes has been described [21]. The authors demonstrated the increase in CCT values and referred it to the results of stromal thickening obtained by using the corneal confocal microscopy [21]. The CCM method was already confirmed to be an effective and repeatable evaluation of diabetic neuropathy [22][23][24].…”
Section: Discussionmentioning
confidence: 97%
“…A study utilizing a rabbit model of alloxan-induced diabetes showed that elevated glucose for 8 weeks leads to significant increases in intraocular pressure, corneal thickness, and stiffness [79]. In human studies, DM resulted in a significant increase in corneal thickness by as much as 19% compared to non-DM controls with cases of neuropathy or elevated HbA 1C showing the highest change in thickness [80,81,82], though others have reported no significant difference in corneal thickness in DM [83,84]. Moreover, biomechanical changes in the cornea as a result of DM have shown conflicting results.…”
Section: Effects Of Dm and Kc On Corneal Structurementioning
confidence: 99%